ANALYZING EMPLOYEE ENGAGEMENT AMONG GENERATION Z: A LITERATURE REVIEW BASED ON JOB DEMANDS-RESOURCES MODEL, SOCIAL EXCHANGE THEORY, AND SELF-DETERMINATION THEORY - Agustinus Toko Susetio (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
This paper presents a systematic literature review on the factors influencing employee engagement among Generation Z based on Job Demand-Resource Model, Social Exchange Theory, and Self Determination Theory. By examining empirical studies focusing exclusively on Generation Z employees, this review identifies key factors: psychological (job stress), leadership style, organizational factors (organizational support, organizational commitment, work meaningfulness, wellbeing, value fit), work life balance, and workplace flexibility. Findings from various studies are combined to formulate strategic recommendations for developing managerial policies and work environments adaptive to the unique characteristics of Generation Z in the lens of Job Demand-Resource Model, Social Exchange Theory, and Self Determination Theory. The results indicate that interventions targeting key factors identified in this review are critical to enhancing employee engagement among Generation Z